D-branes from matrix factorizations - Hori, Kentaro; Walcher, Johannes (Arxiv, 2004)
B-type D-branes can be obtained from matrix factorizations of the Landau-Ginzburg superpotential. We here review this promising approach to learning about the spacetime superpotential of Calabi-Yau compactifications. We discuss the grading of the D-branes, and present applications in two examples: the two-dimensional torus, and the quintic.